DETERMINATION OF THE BEST NATURAL GAS UTILIZATION SCENARIO BASED ON ECONOMIC ANALYSIS IN L AND W FIELDS - Firnanto, Andrean
Natural gas availability for domestic needs at affordable prices can create a beneficial chain effect on the entire national economy. Indonesia, with its total gas reserves of 142.72 TSCF, needs continue to develop along with economic growth, population, and changes in energy consumption patterns. In order to keep fulfilling energy needs, the Indonesian government is trying to increase the utilization of domestic natural gas by encouraging the development of gas infrastructure. Since there is the various option of natural gas utilization, the best end-gas product is determined to derive the maximum added value. In this study, surface facility design is conducted for selecting the best natural gas utilization routes at “L” and “W” Field. The selected gas route is then analyzed by considering technical and economic aspects. In order to determine how those aspects will affect, several models are created, and sensitivity analysis using Gas Routes Calculator software is conducted. The simulation presents NPV as well as wellhead gas price calculation and parameter sensitivity in gas rate, gas product price, capital expenditure, and operational expenditure for all models. The most profitable scenario is determined by comparing the NPV and optimum diameter of the pipeline. An analysis is also conducted in another gas utilization to identify its critical parameter value so as it can be more profitable than the best product. The result of this study shows the electricity has the best-added value gas utilization, and the surface facility has been designed on the suitability of the gas field properties. The technology used on the surface facility includes a gas processing unit, unit-processing facilities, and pipeline unit. The most profitable scenario reaches NPV of USD 768 million by choosing pipeline diameter of 16 inches as an optimum technical result. Sensitivity analysis concluded that gas rate and product price would be the most sensitive parameter in NPV and net-back value, respectively. Other gas utilization route needs increasement of minimum IRR and adjustment in discount rate the best product.